Leadership Practices, Adversity Quotient, And School-Based Management Practices In The New Normal: A Descriptive-Correlational Approach (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
This study investigated the relationship between the leadership practices, adversity quotient, and school-based management practices in the new normal. It employed a descriptive-correlational design with an online survey as the primary data collection tool. The respondents are 104 school heads and 597 teachers from public elementary schools in the City Schools Divisions of Biñan, Cabuyao, Calamba, and Sta. Rosa. Frequency Count, Percentage, Mean, Standard Deviation, and Pearson Product Moment of Correlation were the statistical tools utilized to analyze and interpret the data gathered. The findings revealed that school heads highly practiced the new normal leadership practices in terms of adaptability, decision-making, and planning and implementation as perceived by teachers. For the adversity quotient, teachers indicated below average adversity quotient while the school heads indicated average adversity quotient. The respondents assessed the extent of SBM practices as the presence of evidence indicating practices and procedures satisfying quality standards. Correlation analyses denoted a significant relationship between perceived school heads' leadership practices and assessed SBM practices and between teachers' adversity quotient and assessed SBM practices. Only the control dimension of the adversity quotient of school heads indicated a significant relationship with assessed SBM practices in terms of leadership and governance, accountability and continuous improvement, and management of resources.